Fatigue Shear Strength of Slender Web Plate Girders (Malaysian Journal of Civil Engineering, 2018)
A study on the fatigue strength of slender web plates subjected to repeated shearloading is described herein. A series of tests on 20 girders with slender web wascarried out. The girders were subjected to cyclic loading of a certain range up tothe formation of fatigue cracking. Stresses along the welded connection betweenthe webs and flanges were measured during the tests. The correlation between thestresses and number of cycles of loading at failure was analysed and a new fatigueresistant curve was developed and incorporated into the standard design curve offatigue resistant given in BS 5400:Part 10 and EC 3:Chapter 9. The resistant tofatigue failure for the welded web under shear loading was found to be highcompared to other standard detail categories.